«Una beffa [...] fatta da una donna a uno solenne religioso»: l’arte della manipolazione verbale ed emotiva nel Decameron III 3 - Maślanka-Soro, Maria (Studia Romanica Posnaniensia, 2018)
Boccaccio’s Decameron is, as we know, the supreme achievement of the medieval narratio brevis. The art of speaking and, in general, of the proficient use of words, is what distinguishes the “gentile brigata” of ten young men and women who articulate and advance the new ars narrandi. Its role is crucial in many of the novellas in The Decameron: thanks to their capacity to persuade, or rather to manipulate their listeners verbally, many of its male and female protagonists manage to avoid dangers and unpleasant situations, or to get what they want: love, money, or other advantages. Particularly two of the male protagonists, ser Ciappelletto and frate Cipolla, excel others in verbal fraud and mockery. The anonymous protagonist of the third novella of the Third Day is neither as famous nor as examined by critics, even though she is very clever in her rhetorical and theatrical skills. The purpose of this essay is to analyse the strategies of verbal and emotional manipulation which lead her to seduce a “valoroso uomo di mezza età” with the involuntary help of the simple-minded and credulous friar.